Anomalous Connection of the Right Pulmonary Vein to the Coronary Sinus in a Young Infant - Chi-Lin Ho; I-Chen Tsai; Ming-Chih Lin; Sheng-Ling Jan; Yun-Ching Fu (Pediatrics and Neonatology)
Partial anomalous pulmonary venous connection (PAPVC) is a rare congenital heart disease. Among previous cases, anomalous connection of the right pulmonary vein (RPV) to the coronary sinus (CS) was seldom reported. Here, we report an 8-month-old girl, initially presenting with congestive heart failure, who had this rare anomaly with moderate-sized secundum atrial septal defect (ASD). After confirmation by multi-detector row computed tomography (MDCT) and cardiac catheterization, the infant underwent a successful surgical repair. To our knowledge, this is the first reported infant with this kind of rare anomaly.